Designing of SSSC-based damping controller using bacterial foraging algorithm to improve power system stability. (1st January 2014) - Panda, Gayadhar; Rautraya, Prasant Kumar
This paper proposes a design of bacterial foraging optimisation-based (BFO) SSSC controller for damping low frequency oscillations in a single-machine infinite-bus power system. The oscillations in power systems have to be taken seriously when the fault occurs in any part of the system, or else this might lead to the instability mode and shutting down of the power system. The proposed controller is formulated as an optimisation problem to minimise a time-domain-based objective function by employing BFO technique. The performances of the proposed controller are evaluated under different loadings for single-machine infinite-bus power system. The results obtained from simulations validate the effectiveness of proposed controller and tuning approach for power system stability improvement.